Character Building through Scouts Extracurricular Activities: A Case Study at Private Madrassa Kudus Indonesia - Subaidi, Subaidi; Mustaqim, Muh.; Tantowi, Ahmad (Technium Social Sciences Journal, 2023)
This study describes character building through scout extracurricular activities at a private madrassa in Kudus city Indonesia. This research approach is qualitative, to reveal and understand the reality in Private Madrasah Banat Kudus. Data collection techniques through interviews, observation, and documentation study. The research findings are the interrelation of scout extracurricular activities by building student character, namely the learning outcomes in the classroom with attitudes and skills that students need to develop to have noble values of characters, including religious, honest, disciplined, democratic, socially caring, caring environment, tolerance, deliberation, help each other, communicative and appreciate diversity.